2014
DOI: 10.1186/1475-2875-13-316
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic determinants of ownership and use of treated bed nets in Nigeria: results from a cross-sectional study in Cross River and Bauchi States in 2011

Abstract: BackgroundPoor people bear a disproportionate burden of malaria and prevention measures may not reach them well. A study carried out to examine the socio-economic factors associated with ownership and use of treated bed nets in Cross River and Bauchi States of Nigeria took place soon after campaigns to distribute treated bed nets.MethodsA cross-sectional household survey about childhood illnesses among mothers of children less than four years of age and focus group discussions in 90 communities in each of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 9 publications
6
23
0
Order By: Relevance
“…This is in line with previous studies which showed that people can be acquainted with the knowledge of malaria transmission, prevention and control irrespective of their educational status [27,28]. This is however in contrast to the report of Adedotun et al, [29], Eteng et al, [30] and Dawaki et al, [31] who noted that the level of education signi cantly in uence the knowledge, attitude and practices of people which in turn can lead to reduced malaria infection. Similarly, those who travelled to rural area or village in this study area had higher malaria prevalence and density.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with previous studies which showed that people can be acquainted with the knowledge of malaria transmission, prevention and control irrespective of their educational status [27,28]. This is however in contrast to the report of Adedotun et al, [29], Eteng et al, [30] and Dawaki et al, [31] who noted that the level of education signi cantly in uence the knowledge, attitude and practices of people which in turn can lead to reduced malaria infection. Similarly, those who travelled to rural area or village in this study area had higher malaria prevalence and density.…”
Section: Discussionsupporting
confidence: 89%
“…It has been explained in the Cross River state of Nigeria [29] that educated parents may be better able to appreciate the importance of treated nets in malaria prevention and to understand the information included in the public awareness campaigns which will eventually influence bednet usage by their families. Such associations have also been shown by in Kinshasa-DRC by Pettifor et al [30] and Ndjinga and Minakawa [31] and in Mfou-Cameroon by Tchinda et al [3].…”
Section: Discussionmentioning
confidence: 99%
“…Variation in wealth has been linked to human exposure in multiple vector‐borne disease systems across resource‐wealthy and resource‐poor nations . This is due, in part, to changes in mosquito breeding habitats around the home, land cover, availability of other food sources, access to public health infrastructure (e.g., vaccines and therapeutics), and access to education and to intervention strategies, such as bed nets . The proportion of a population of a given age or sex can also influence exposure to vector‐borne disease via age‐, sex‐, or even pregnancy‐related differences in human behavior .…”
Section: Conclusion/future Research/unanswered Questionsmentioning
confidence: 99%
“…154,155 This is due, in part, to changes in mosquito breeding habitats around the home, 156 land cover, [157][158][159][160][161] availability of other food sources, [162][163][164] access to public health infrastructure (e.g., vaccines and therapeutics), 165 and access to education and to intervention strategies, such as bed nets. 166,167 The proportion of a population of a given age or sex can also influence exposure to vector-borne disease via age-, sex-, or even pregnancy-related differences in human behavior. [166][167][168] Current mapping efforts, which highlight the transmission risk of CHIKV and ZIKV globally, fail to incorporate these factors.…”
Section: Conclusion/future Research/unanswered Questionsmentioning
confidence: 99%
See 1 more Smart Citation